Post-operative Recovery Assessment of Urinary Tract Dysfunction Following Radical Hysterectomy for Cervical Cancer Patients: Kajian Pemulihan Fungsi Berkemih pada Pasien Kanker Serviks Pascahisterektomi Radikal - Laila Nuranna; Sang A F Adi Kusuma (Indonesian Journal of Obstetrics and Gynecology, 2018)
Abstract Objectives: To assess the length of recovery phase in urinary tract dysfunction following radical hysterectomy for cervical cancer patients in Ciptomangunkusumo Hospital. Methods: This survey study was conducted in Cipto Mangunkusumo Hospital from September 2016 to May 2017. Subjects were cervical cancer patients from stage IA2 to IIA2 underwent radical hysterectomy. Suprapubic catheter (SPC) was inserted to observe the urine production after procedure. Patients were then directed for bladder training protocol involving clamping and opening SPC. Sensation of bladder fullness followed by spontaneous micturition were recorded. Measurement of post voiding residual (PVR) urine volume after spontaneous micturition until less than 100 mL was considered as resolution of urinary tract dysfunction. The average days of every achieved phase were then calculated. Results: Twenty-nine subjects underwent radical hysterectomy during observation period. But only 21 subjects continued the bladder training protocol and recorded for the recovery phases. The average time needed to obtain sensation of bladder fullness and spontaneous micturition were 7.57 ± 4.78 days (median 5 days, minimum 3 days, maximum 22 days)and 8 ± 5.21 days (median 6 days, minimum 3 days, maximum 23 days). The objective PVR urine became less than 100mL was obtained after 21.42 ± 18 days (median 18 days, minimum 7 days, maximum 74 days). Conslusion: Following radical hysterectomy, recording the recovery phase of urinary tract dysfuction is essential to ensure complete resolution. Complete resolution of the urinary dysfunction is achieved after 21.42±18 days in average (median 18 days, minimum 7 days, maximum 74 days). Keywords: cervical cancer, radical hysterectomy, urinary tract dysfunction, post voiding residual volume. Abstrak Tujuan: Menilai masa pemulihan disfungsi saluran kemih setelah histerektomi radikal pada pasien kanker serviks di RSUPN Ciptomangunkusumo. Metode: Studi survei dilakukan di RSUPN Cipto Mangunkusumo dari September 2016 hingga Mei 2017. Subjek penelitian terdiri dari pasien kanker serviks stadium IA2 hingga IIA2 yang menjalani histerektomi radikal. Kateter suprapubik (SPC) digunakan sebagai alat untuk memantau produksi urin pasca operasi. Pasien diinstruksikan untuk mengikuti protokol bladder training yaitu melalui prosedur menutup dan membuka kateter. Rasa sensasi ingin berkemih dan berkemih spontan. Pengukuran residu volume urin pasca berkemih dibawah 100mL dianggap merupakan indikator pemulihan disfungsi saluran kemih. Rata-rata hari dari setiap fase kemudian dihitung. Hasil: Dua puluh sembilan subjek didapatkan selama penelitian. Namun, hanya 21 subjek yang dapat mengikuti protocol bladder traning dan dicatat perkembangan pemulihannya. Rata-rata hari yang diperlukan untuk merasakan sensasi berkemih dan berkemih spontan adalah 7,57 ± 4.78 hari (median 5 hari, minimum 3 hari, dan maksimum 22 hari) dan 8 ± 5.21 hari. (median 6 hari, minimum 3 hari dan maksimum 23 hari) Rata-rata hari untuk mencapai residu urin di bawah 100 mL adalah 21.42 ± 18 (median 18 hari, minimum 7 hari, dan maksimum 74 hari). Kesimpulan: Setelah prosedur histerektomi radikal, pencatatan masa pemulihan penting untuk dipantau untuk memastikan pemulihan lengkap. Rata-rata hari yang diperlukan untuk pemulihan adalah 21.42 ± 18 hari (median 18 hari, minimum 7 hari, dan maksimum 74 hari). Kata kunci: kanker serviks, histerektomi radikal, disfungsi saluran kemih, volume residu paska berkemih.